Teaching non-traditional students: EFL teacher’s experiences, challenges, and future recommendations - Marzulina, Lenny; Erlina, Dian; Holandyah, Muhammad; Herizal; Astrid, Annisa; Putri, Himah Zalifah; Wahyuni, Nurul (Indonesian Research Journal in Education |IRJE|, 2025)
This qualitative case study aimed to identify the challenges faced by English as a Foreign Language (EFL) teachers at the First Class Correctional Institution for Children in Palembang, South Sumatra, Indonesia, while teaching English to young inmates. The participants included two high school English teachers from this institution. Data collection was conducted through interviews to obtain in-depth descriptions of the difficulties encountered. A thematic analysis was employed to evaluate the data and highlight the specific difficulties faced by the English teachers. The findings revealed four primary challenges experienced by the teachers in their efforts to teach English to young inmates: 1) issues related to time management, 2) students’ negative attitudes, 3) a lack of available textbooks, and 4) inadequate classroom conditions. These challenges significantly impact the effectiveness of English instruction within this unique educational environment.